Effect of prednisone on Th17/Treg immune balance in adult patients with primary nephritic syndrome - YANG Guo-sheng; ZHOU Huan; ZHANG Xin; HE Yong; WANG Xiao-hui (Linchuang shenzangbing zazhi)
Objective To investigate whether the Th17/Treg immune balance was broken in adult patients with primary nephritic syndrome and to explore the possible role of Th17/Treg immune balance in the pathogenesis of primary nephritic syndrome and how prednisone inflences the Th17/Treg immune balance during treatiment of adult PNS.Methods Twenty-five healthy volunteers served as healthy controls and 65 prednisone-effective adult patients with PNS were enrolled in this study.Blood samples were obtained from healthy control group and patients with PNS before and after treatment The frequencies of peripheral Th17 and Treg were evaluated by flow cytometry.The concentrations of plasma IL-17 and IL-10 were tested by ELISA.Proteinuria levels were detected by automatic biochemical analyzer.Correlations between peripheral Th17,Treg frequencies and concentrations of related cytokines IL-17,IL-10 were analyzed.Correlation between Th17/Treg ratios and proteinuria levels was analyzed.Results As compared with healthy controls,the frequencies of peripheral Th17 increased significantly(2.44%± 0.58%vs.0.93%± 0.41%),and those of Treg decreased significantly(2.28%± 0.63%vs.3.83%± 1.06%).After prednisone treatment,PNS patients exhibited a significant decrease in the frequencies of Th17(1.02%±0.51%),and the frequencies of Treg increased markedly(3.69%± 0.82%).All these results showed significant differences.Besides,IL-17 concentrations were positively correlated with frequencies of peripheral Th17,and EL-10 concentrations were positively correlated with frequencies of peripheral Treg.Th17/Treg ratios were positively correlated with proteinuria levels.Conclusions Th17/Treg imbalance may be involved in the pathogenesis of primary nephritic syndrome.Effective prednisone therapy may maintain Th17/Treg immune balance in adult PNS patients.Th17/Treg ratios may be used as an accessory diagnosis marker for adults with PNS and therapeutic effect evaluation for prednisone treatment